Effects of personalized movement models in virtual reality on pain expectancy and motor behavior in patients with chronic back pain: a feasibility study - Kammler-Sücker, Kornelius; Löffler, Annette; Flor, Herta (Virtual reality, 2023)
Cognitive-behavioral therapy (CBT) of chronic pain focuses on behavioral, cognitive, affective and social factors that play a role in the transition from acute to chronic pain, which often is initially caused by a specific event but then takes on “a life of its own”. CBT models assume that fear of pain and subsequent avoidance behavior contribute to pain chronicity and the maintenance of chronic pain. In chronic back pain (CBP), avoidance is often addressed by teaching patients to reduce pain behaviors (such as guarding and bracing that may become dysfunctional over time) and increase healthy behaviors (such as physical exercise and meaningful social activities). The current study explored if personalized virtual movement models (doppelganger avatars), who maximize model-observer similarity in virtual reality (VR), can influence fear of pain, motor avoidance and movement-related pain and function. In a randomized controlled trial, participants with CBP observed and imitated an avatar (AVA, N = 17) or a videotaped model (VID, N = 16) over three sessions, where moving a beverage crate, bending sideward (BS), and rotation in the horizontal plane (RH) were shown. Self-reported pain expectancy, as well as engagement, functional capacity and pain during movements, were analyzed along with range of motion (ROM). The AVA group reported higher engagement with no significant group differences observed in ROM. Pain expectancy increased in AVA but not VID over the sessions. Pain and limitations did not significantly differ. However, we observed a significant moderation effect of group, with prior pain expectancy predicting pain and avoidance in the VID but not in the AVA group. This can be interpreted as an effect of personalized movement models decoupling pain behavior from movement-related fear and pain expectancy. Thus, personalized virtual movement models may provide an additional tool for exposure and exercise treatments in cognitive-behavioral treatment approaches to CBP.